Quality of Life, Treatment Seeking Pathways and Out of Pocket Expenditure of parents with children with Autism Spectrum Disorder (ASD) in South Delhi - Islam, Farzana; Abdul Salam, Afrah Saleef; Gautam, Richa; Kashyap, Varun; Roy, Sushovan (Indian Journal of Community Health, 2024)
Background: Autism is a neurodevelopment disorder requiring continuous preventive, curative and rehabilitative management of child. Taking care of these children leads to parents face various challenges. Lack of awareness, associated stigma, misdiagnosis, inappropriate management impacts parents' lives in various aspects. Objectives: To assess quality of life of the parents of ASD children, find out various treatment-seeking pathways adopted by them, and estimate out-of-pocket expenditure for childcare. Methodology: Cross-sectional mixed method study was conducted for assessment of quality of life of parents (WHO-QOL BREF), out-of-pocket expenditure, treatment-seeking pathways opted by parents for ASD management. Results: Quality of life of parents were found to be affected in various domains, however psychological domain was most influenced. Age of parents had an impact on social domain. Delays in the identification of symptoms, confirmation of diagnosis, Lack of availability of treatment services, and non-integration of rehabilitative services were major loopholes in the treatment seeking. The median out-of-pocket expenditure was 16% of monthly family income. Conclusion & recommendation: Community awareness, medical fraternity sensitization, integration of all services for management and rehabilitation are keys towards better quality of life for parents. Financial support through health programs, NGOs, or insurance is a much-needed reform to reduce catastrophic health expenditure.